DIGITAL EDUCATIONAL TECHNOLOGIES IN TEACHING A FOREIGN LANGUAGE IN HIGHER EDUCATION - I. N. Karapetova; M. K. Kharina (Современная наука и инновации)
Distance learning is now rapidly becoming more important. Universities compete with each other around the world, trying to attract the best students and teachers from all over the world. The digital age has changed the way people live, the way they receive education and upbringing. Everything around us is changing, and the attitude to learning must change accordingly. The role of international education is significantly increasing, since it is vital for the modern world to develop its own culture, develop and move forward. It is also vital to learn foreign languages in order to keep up with the times. Today, the knowledge of foreign languages opens a window to a large global world with its wide flow of information and innovation. At present, the modernization of educational system in Russia is associated with innovative processes in the organization of foreign language teaching. The main task of the teacher at the present stage is to choose methods and forms of organization of educational activities of students that optimally meet the goal. In recent years, the question of using new information technologies in higher education has been raised more often. Since the main goal of teaching foreign languages is the formation and development of the communicative culture of students, training in practical foreign language acquisition is a priority in education. The article discusses the possibilities of using electronic educational resources to ensure interactivity of the learning process. The study attempts to identify the features of the use of digital educational technologies in teaching a foreign language in higher education, advantages and disadvantages.